Simple and green route for fabrication of a nanostructured of the graphene‐Fe3O4@PANI for the photovoltaic activity. (10th December 2021) - Sadegh, Fatemeh; Modarresi-Alam, Ali Reza; Sadegh, Negar; Bahrpeyma, Abdolhamid; Shabzendedar, Sahar; Kerman, Kagan; Noroozifar, Meissam
Highlights: Synthesis of Gr|Fe3 O4 @PANI nanocomposite via simple, low cost, one step, green, and in-situ polymerization method. An unusual indirect transition and increase of triplet state of excitons arising from a spin-orbit coupling created by Fe3 O4 . The fabrication of single-layer polymer solar cells using Gr|Fe3 O4 @PANI as active layer. The donor and acceptor mechanisms for the electron transfer in polymer solar cell are proposed. Abstract: In this work, for the first time, Gr (graphene)|Fe3 O4 @PANI nanocomposite was synthesized from graphite, aniline-HCl and FeCl3 .6H2 O via a simple in-situ and green route as the active layer for photovoltaic application. The proposed nanocomposite was characterized by FT-IR, SEM, TEM, UV-vis spectroscopy, XRD technique, and then the thermal, magnetic, electrochemical, and photovoltaic properties investigated. The energy gap was calculated, and it is noticed that the optical band gap of nanocomposite fallows an indirect transition, arising from a strong spin-orbit coupling created by Fe3 O4 in the Gr|Fe3 O4 @PANI nanocomposite. Next, polymer solar cell (PSC) based on this nanocomposite was fabricated with a simple device structure of FTO│ TiO2│ Gr|Fe3 O4 @PANI│ Al. The photovoltaic properties of the cells have been evaluated under AM 1.5G illumination at 60 mW/cm 2 with a solar simulator. A power conversion efficiency (PCE) of 1.81% was observed with a short circuit current (Jsc ) of 4.14 mA/cm 2, an open-circuit voltage (Voc ) of 0.71 V, which indicates this kind of conjugated polymer should be a promising material in the application of polymer solar cells. Graphical abstract: Image, graphical abstract